Efeito da infecção pulpar e periodontal na glicemia de ratos Wistar - Pereira, Thamiris Tieni [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The objective of this work was to evaluate the interrelationship between pulp and/or periodontal diseases and diabetes systemic disease by glycemic monitoring. 80 mice of the Wistar family were used and divided into 8 groups of 10 animals: G1 - healthy mice; G2 - Pulp disease affected mice; G3 - periodontal disease affected mice; G4 - pulp and periodontal diseases affected mice; G5 - diabetic mice; G6 - diabetes and pulp disease affected mice; G7 - diabetes and pulp disease affected mice; G8 - diabetes, pulp and periodontal diseases affected mice. The diabetes was induced by applying streptozotocin, the pulp infection by the dental pulp exposure to oral environment and the periodontal disease by the manufacturing of obstruction of the dental cervix. The animals were assessed via glycemic monitoring throughout the experimental period and sacrificed after 30 dias. Was possible notice that in all groups of mice nondiabetic glucose curves were similar. However, any local diseases association was enough to raise the glucose levels of diabetic animals even higher. It was concluded that pulp disease alone not influences on blood glucose in diabetic mice, but periodontal disease alone or disease associated with the pulp influences glucose levels in diabetic mice

O objetivo deste trabalho foi avaliar a inter-relação entre as doenças pulpar e/ou periodontal e a doença sistêmica diabetes, por meio do monitoramento glicêmico. Foram utilizados 80 ratos da linhagem Wistar divididos aleatoriamente em 8 grupos de 10 animais: G1 - ratos saudáveis; G2 - ratos com doença pulpar; G3 - ratos com doença periodontal; G4 - ratos com doença pulpar e periodontal; G5 - ratos diabéticos; G6 - ratos diabéticos com doença pulpar; G7 - ratos diabéticos com doença periodontal; G8 - ratos diabéticos com doença pulpar e periodontal. A diabete foi induzida pela aplicação de estreptozotocina, a infeção pulpar pela exposição da polpa dentária ao meio oral e a doença periodontal pela confecção de amarria junto ao colo dentário. Os animais foram monitorados por avaliação glicêmica durante todo o período experimental e sacrificados após 30 dias. Pôde-se observar que em todos os grupos de ratos não diabéticos as curvas glicêmicas foram semelhantes. Entretanto, qualquer associação da doença local foi suficiente para elevar ainda mais o nível glicêmico dos animais diabéticos. Pôde-se concluir que a doença pulpar isolada não influencia de forma significante na glicemia de ratos diabéticos, porém a doença periodontal isolada ou associada com a doença pulpar influencia os níveis glicêmicos de ratos diabéticos
Keywords: Diabetes mellitus; Doenças periodontais; Ratos Wistar